Solicitation and Auditor Reporting Decisions - Jeter, Debra C.; Shaw, Pamela Erickson (The Accounting Review, 1995)
[Many states removed their bans on direct univited solicitation during the 1980s, while others retained their restrictions. This period of contrast provides an opportunity to examine and provide insight into associations that exist among information dissemination, client-auditor alignment, and auditor independence. Although concerns have been voiced that recent changes in competitive conditions in the audit market are detrimental to audit quality, we present arguments and evidence to the contrary. Results of a logistic regression analysis suggest that, ceteris paribus, auditors in the market allowing solicitation are more likely than those in the market banning solicitation to issue a nonstandard report.]